Chapter La signoria rurale in Italia alla fine del medioevo e le istituzioni ecclesiastiche - Varanini, Gian Maria (Reti Medievali E-Book, 2023)
The essay illustrates some aspects of the control exercised by Italian rural lords in the 14th and 15th centuries over ecclesiastical institutions located on lordly territory (parish churches, chapels, monasteries). It dwells in particular on the rights of jus patronatus and relations with the ecclesiastical hierarchies.